Hinterland Access Regimes in Seaports - de Langen, Peter W.; Chouly, Ariane (European Journal of Transport and Infrastructure Research, 2004)
Seaports serve hinterlands. Various inland modes such as road, rail, inland waterways and pipeline are used to access the hinterland. The quality of the access to and from the hinterland differs between seaports and affects their competitiveness. The quality of the hinterland access depends among others on the behaviour of a large variety of actors, such as shipping lines, terminal operators, forwarders, the port authority and the national/regional government. Therefore, effective hinterland access is at least partially an organisational challenge. Together these actors create a ‘hinterland access regime’. The analysis of this regime is central in this paper. First, the relevance of hinterland access for seaports is briefly discussed. Second, the term ‘hinterland access regime’ is defined and the theoretical framework presented in De Langen (2004) is used to analyse the quality of the hinterland access regime. Third, survey results on the quality of the hinterland access regime in three seaport clusters, Rotterdam, Durban and the Lower Mississippi Port Cluster (LMPC) are discussed. This analysis shows major differences between hinterland access regimes. Fourth, opportunities to improve the hinterland access regime in these three ports are discussed.